Menelusuri Keberagamaan Jamaah Majelis Tattoo di Kota Bandung - Deden Nurfaizal; Bambang Qomaruzzaman (Jurnal Iman dan Spiritualitas, 2021)
This research focuses on the growing religious community in Bandung, namely Bandung Tattoo Council congregation, what kind of situation leads individuals to religion; that is the starting point of this study. This study aims to determine the motivation and religious expression of the Majelis Tato plural religious experience. This study used qualitative research methods. Data in this study were obtained through primary data sources coming from field information from administrators and members of the Majelis Tato and sourced from field information, from the surrounding community, and literature with documents, journals, academic research, articles, magazines, and books relating to the religious issues of the Majelis Tato congregation. Data collection techniques using observation and interviews. Data analysis with data collection, data reduction, data presentation, conclusion/verification. This study's results are the motivation of the Bandung Tattoo Council congregation, namely, experiencing the release of inner pressure so that it motivates them to join the Tattoo Council and have a religion (in the context of doing repentance). They feel that their life seems like that and feel the world makes them feel frustrated and makes them tired, so they think there is a need and urge to seek calm. As for the Tattoo Council congregation's religious experience, almost all of them depart from past behavior that they consider sinful to seek guidance through religion. Religious experience in deeds, namely, advice on reading and writing the Koran, guidance on worship practices, direction on memorizing Al-Qur'an, and personal recommendation.